2017
DOI: 10.1186/s13072-017-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Histone and DNA methylation control by H3 serine 10/threonine 11 phosphorylation in the mouse zygote

Abstract: Background In the mammalian zygote, epigenetic reprogramming is a tightly controlled process of coordinated alterations of histone and DNA modifications. The parental genomes of the zygote show distinct patterns of histone H3 variants and distinct patterns of DNA and histone modifications. The molecular mechanisms linking histone variant-specific modifications and DNA methylation reprogramming during the first cell cycle remain to be clarified.ResultsHere, we show that the degree and distribution of H3K9me2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…In agreement with this finding, a phosphatase complex Repoman1/PP1 that dephosphorylates H3S10 and H3S28 [71], regulates the formation of heterochromatin and is necessary and sufficient for HP1 recruitment and repressive histone modifications [41]. Also in mouse embryo model, H3S10ph limited the expansion of heterochromatin features: H3K9me2 and DNA methylation [72]. Furthermore, H3S10ph positively affects H3K4 methylation by making histone H3 a more attractive substrate for a SET domain of KTM2A/MLL1 complex and enables this methyltransferase complex to outcompete HP1-and Polycomb-mediated chromatin condensation [73], indicating that safeguarding nucleosomes from heterochromatin marks leads to reinforcement of factors associated with active transcription.…”
Section: H3s10 Phosphorylation In the Regulation Of Transcription In supporting
confidence: 68%
“…In agreement with this finding, a phosphatase complex Repoman1/PP1 that dephosphorylates H3S10 and H3S28 [71], regulates the formation of heterochromatin and is necessary and sufficient for HP1 recruitment and repressive histone modifications [41]. Also in mouse embryo model, H3S10ph limited the expansion of heterochromatin features: H3K9me2 and DNA methylation [72]. Furthermore, H3S10ph positively affects H3K4 methylation by making histone H3 a more attractive substrate for a SET domain of KTM2A/MLL1 complex and enables this methyltransferase complex to outcompete HP1-and Polycomb-mediated chromatin condensation [73], indicating that safeguarding nucleosomes from heterochromatin marks leads to reinforcement of factors associated with active transcription.…”
Section: H3s10 Phosphorylation In the Regulation Of Transcription In supporting
confidence: 68%
“…The transcriptional analysis of ERα-target genes under different epigenetic inhibitors and knockdowns provides key insight into the crosstalk regulation of transcription. While it was previously shown that PAD2 is necessary for transcription of several ERα-target genes, 60 this is the first work to suggest that a concurrent K27 demethylation event is also required. By pretreating with the KDM inhibitor GSK-J4, transcription was blocked at many of these promoters similarly to when PAD2 is knocked down.…”
Section: Discussionmentioning
confidence: 76%
“…While the effect of substrate modifications has a clear impact on enzymatic activity, the multitude of possible histone modifications and modifying enzymes is staggering. Previous studies have cited crosstalk between two or three modifications with gene expression changes. In this work, we extend this hypothesis to EZH2-catalyzed H3K27 methylation and PAD2-catalyzed H3R26 citrullination.…”
Section: Discussionmentioning
confidence: 76%
“…Histone phosphorylation is apparently part of the complex interplay between other epigenetic marks, such as histone acetylation, histone methylation and DNA methylation. Increased histone phosphorylation has been found to maintain certain histone and DNA methylation marks early in a mouse zygote [154]. Similarly, evidence indicates that increased histone 3 Serine 10 (H3S10) phosphorylation during meiosis and mitosis is related to chromatin condensation and gene repression with increased methylation of H3K9 [155], but this modification can also be associated with gene activation in some instances.…”
Section: Epigenetic Regulation Of Astrocyte Development and Functionmentioning
confidence: 99%